Influencing factors and research progress on humanistic caring ability of nursing students (护生人文关怀能力影响因素及研究进展) - ZHOU Jie (周洁); CHEN Hong (陈宏); TANG Ling (唐玲) (中西医结合护理)
Humanistic care is the core and essence of nursing. Nursing internship is the necessary stage for transitioning from the role of nursing student to professional nurse. This paper summarizes the factors influencing the current situation of nursing students' humanistic care ability, and puts forward the cultivation strategies to improve the humanistic care ability of nursing students, so as to provide reference for the reform of nursing humanistic education and promote the comprehensive development of nursing students. (人文关怀是护理的核心与本质, 护理实习生是护士从学校走向护理工作岗位的必经阶段。本文总结了目前护生人文关怀能力的现状、影响因素, 提出了提高护生人文关怀能力的培养策略, 以期为护理人文教育改革提供参考, 促进护生全面发展。)